Infeksi Saluran Kemih Nosokomial: Faktor Risiko, Patogen, dan Strategi Pencegahan - Nisrina Talida Hasan; Sutarto, Sutarto; Nanda Fitri Wardani; Novita Carolia (Journal of Medical Practice and Research, 2025)
Nosocomial urinary tract infections (NUTI) are one of the most common healthcare-associated infections, particularly in patients with urinary catheters. This article aims to examine the risk factors, causative pathogens, and prevention strategies for NOS based on current literature. The method used was a structured literature review with the PRISMA approach through a search of articles in the Scopus and PubMed databases published between 2020 and 2025. Articles that met the inclusion criteria were analyzed descriptively. The review results showed that the main risk factors included duration of catheter insertion, intensive care unit stay, advanced age, comorbidities, and service factors such as re-catheterization and antibiotic use. The causative pathogens were dominated by Gram-negative bacteria, particularly Escherichia coli, Klebsiella pneumoniae, and Acinetobacter baumannii, with varying distributions across care settings. Effective prevention strategies include limiting catheter use and duration, implementing aseptic technique, close monitoring in high-risk units, and innovation in catheter technology. In conclusion, prevention of nosocomial urinary tract infections requires a comprehensive approach that integrates patient, pathogen, and health care system aspects.